Diversity of new Russian bread wheat cultivars according to leaf rust resistance genes - E. I. Gultyaeva; E. L. Shaydayuk; V. V. Veselova; R. E. Smirnova; E. V. Zuev; A. G. Khakimova; O. P. Mitrofanova (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Cultivation of resistant cultivars is an effective method of wheat protection against leaf rust. The purpose of this work was to characterize the juvenile leaf rust resistance of bread wheat cultivars listed in the State Register for Selection Achievements in 2021 and identify their Lr genes using molecular markers.Materials and methods. The material included 18 cultivars of winter bread wheat and nine spring ones. Juvenile resistance in the seedling phase was assessed with two test clones (kLr9 и kLr19) and the Krasnodar population of Puccinia triticina Erikss. Molecular markers were used to identify 18 Lr genes.Results and discussion. A high level of resistance (score 0 or 0;) was shown by cvs. ‘Khamdan’, ‘Sharm’ and ‘Omskaya 44’; moderate resistance (score 2, 2+) by ‘Albidum 2030’. Reactions of ‘Polina’, ‘Rossyp’, ‘Status’, ‘Balkysh’ and ‘Bogema’ were variable. The studied cultivars did not contain juvenile genes Lr9, Lr24, Lr25, Lr28, Lr29, Lr39, Lr47 or Lr66 and adult plant resistance genes Lr21 and Lr35. Markers of identifiable genes were not detected in cv. ‘Sharm’, highly resistant to leaf rust. ‘Khamdan’ had an ineffective Lr10 gene and a partial resistance gene Lr34, which offered no protection in the seedling stage. These cultivars seem to contain additional resistance genes. A high level of resistance to leaf rust in ‘Omskaya 44’ is provided by a combination of the Lr19, Lr26, Lr1 and Lr3 genes. In ‘Nemchinovskaya 85’, the partially effective adult plant resistance gene Lr37 was identified. In other tested cultivars, Lr1, Lr3, Lr10, Lr26 and Lr34 were widely represented.